Double-blind study comparing the in vivo efficacy of two hyaluronic acid products (high and very high molecular weight) in improving skin elasticity in cosmetic treatments. Are all hyaluronic acids the same? Points to bear in mind - González Martín, Mayka; de Assis, Luis Antônio; Perez Gonzalez, Maria de los Lanos; Expósito González, Sandra Exposito González; García Diaz, Maria Begoña (Aesthetic Medicine, 2025)
Background: Hyaluronic acid (HA) is in high demand in aesthetic medicine, leading to a wide variety of products differing in concentration, molecular weight, additives, and delivery methods. Patients often choose HA treatments based solely on the presence of HA, without understanding product-specific indications or effects. However, the formulation and application method significantly influence clinical outcomes.Objective: To compare the effectiveness of two injectable HA products—Restylane® Vital and TKN HA3®—commonly perceived as similar despite differences in their composition and manufacturing.Methods: A split-face study was conducted on 20 subjects. Restylane® Vital was injected on one side of the face, and TKN HA3® on the other. Objective skin elasticity was measured using the Cutometer® MPA 580. Subjective assessments included the Global Aesthetic Improvement Scale (GAIS), completed by both an independent investigator (GAIS-I) and the participants (GAIS-S), along with patient satisfaction questionnaires.Results: Objective measurements showed differences in skin elasticity between the two products, further supported by GAIS-I evaluations. Despite these findings, subjective assessments (GAIS-S and satisfaction questionnaires) indicated that participants perceived both treatments as equally effective, with no clear preference.Conclusions: Although both HA products produce similar visual outcomes and are often used interchangeably, their differing formulations result in distinct clinical effects. This study found that although patients perceived similar results from both products, objective assessments showed that VHMWHA was more effective than modified HA in enhancing skin elasticity.